2013
DOI: 10.1093/cercor/bht200
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cocaine Self-Administration on Dendritic Spine Density in the Rat Hippocampus Are Dependent on Genetic Background

Abstract: Chronic exposure to cocaine induces modifications to neurons in the brain regions involved in addiction. Hence, we evaluated cocaine-induced changes in the hippocampal CA1 field in Fischer 344 (F344) and Lewis (LEW) rats, 2 strains that have been widely used to study genetic predisposition to drug addiction, by combining intracellular Lucifer yellow injection with confocal microscopy reconstruction of labeled neurons. Specifically, we examined the effects of cocaine self-administration on the structure, size, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…Fischer and Lewis rats differ also in their stress response (Dhabhar et al, 1993; Ergang et al, 2015) and impulsivity score (Hamilton et al, 2014; Madden et al, 2008), two features related to vulnerability to addiction. Overall, comparisons between Fischer and Lewis rats in cocaine self-administration have been carried out primarily in relatively short access self-administration paradigm (≤ 6h), rather than extended access (Freeman et al, 2009; Miguens et al, 2015; Rivera et al, 2013). Our laboratory has recently reported that Lewis rats escalate both cocaine and heroin intake to a greater extent than Fischer rats, in a new model of extended access (18h/day for 14 sessions) intravenous self-administration, in which rats are allowed to select the unit dose of drug to self-administer (Picetti et al, 2012; Picetti et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Fischer and Lewis rats differ also in their stress response (Dhabhar et al, 1993; Ergang et al, 2015) and impulsivity score (Hamilton et al, 2014; Madden et al, 2008), two features related to vulnerability to addiction. Overall, comparisons between Fischer and Lewis rats in cocaine self-administration have been carried out primarily in relatively short access self-administration paradigm (≤ 6h), rather than extended access (Freeman et al, 2009; Miguens et al, 2015; Rivera et al, 2013). Our laboratory has recently reported that Lewis rats escalate both cocaine and heroin intake to a greater extent than Fischer rats, in a new model of extended access (18h/day for 14 sessions) intravenous self-administration, in which rats are allowed to select the unit dose of drug to self-administer (Picetti et al, 2012; Picetti et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The reduced cocaine sensitivity in Tg compared to WT rats emerged even with the relatively low cocaine self‐administration doses used in the current study and in some of the related literature (Bertrand et al, ; McIntosh et al, ; Wayman et al, ; Zhu et al, ). Indeed, research investigating this transgenic model should use the higher doses more common in cocaine self‐administration studies (Miguéns et al, ; Morgan, Liu, & Roberts, ) and provide a comparative background across strains. Further, the time taken for dopamine reuptake in striatal slices in HIV‐1 Tg rats is extended compared to WT controls (Javadi‐Paydar et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…VR = variable ratio, FR = fixed ratio, Tg = transgenic. this transgenic model should use the higher doses more common in cocaine selfadministration studies (Miguéns et al, 2015;Morgan, Liu, & Roberts, 2006) and provide a comparative background across strains. Further, the time taken for dopamine reuptake in striatal slices in HIV-1 Tg rats is extended compared to WT controls (Javadi-Paydar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic COC exposure is related to structural changes of the CNS, specifically in areas involved in addiction (MacAskill et al, 2014;Miguens et al, 2015). Repeated treatment with COC has been reported to induce modifications in the architecture of dendrites and the density of dendritic spines on medium spiny neurons in the nucleus accumbens (NAc) and pyramidal cells in the prefrontal cortex (Robinson et al, 2001;Robinson and Kolb, 2004).…”
Section: Dendritic Cell Architecturementioning
confidence: 99%
“…in the hippocampus following COC self-administration. The differential susceptibility to COC among these strains may be attributed to the impact of genetic background on both molecular and behavioral levels (Miguens et al, 2015). The role of reproductive status and the COC treatment on brain structure was also recorded in a study that investigated pregnant and virgin rats.…”
Section: Dendritic Cell Architecturementioning
confidence: 99%